2017
DOI: 10.1038/eye.2017.95
|View full text |Cite
|
Sign up to set email alerts
|

Black patients sustain vision loss while White and South Asian patients gain vision following delamination or segmentation surgery for tractional complications associated with proliferative diabetic retinopathy

Abstract: PurposeThis retrospective comparative case series aims to determine whether patient ethnicity (White versus South Asian versus Black) is related to the outcome of surgical treatment for traction complications of severe proliferative diabetic retinopathy (PDR).SettingMoorfields Eye Hospital London, UK.MethodsAll patients who underwent vitrectomy with, delamination and/or segmentation for PDR over a 5-year period (2009-2014) were reviewed retrospectively. Patients were divided into White, South Asian or Black gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…This is comparable to the visual outcome in the 2016 National Ophthalmic Database report on the outcome of vitrectomy and delamination in the UK in patients of all race/ethnicity [3]. It is however a very different result to that presented by Mastropasqua et al, in which the mean change in acuity in black patients was a loss of virtually 3 logMAR lines [4]. The only other data of which we are aware on the outcome of vitrectomy and delamination in cohorts of black patients were reported by Guthrie et al [8] and Rice & Steffen [9].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This is comparable to the visual outcome in the 2016 National Ophthalmic Database report on the outcome of vitrectomy and delamination in the UK in patients of all race/ethnicity [3]. It is however a very different result to that presented by Mastropasqua et al, in which the mean change in acuity in black patients was a loss of virtually 3 logMAR lines [4]. The only other data of which we are aware on the outcome of vitrectomy and delamination in cohorts of black patients were reported by Guthrie et al [8] and Rice & Steffen [9].…”
Section: Discussionsupporting
confidence: 76%
“…A recent comparative analysis by Mastropasqua et al found that black patients did not benefit from vitrectomy and delamination surgery for tractional complications of proliferative diabetic retinopathy [4]. They reported a mean decline in visual acuity of 0.26 logMAR by 6 months post-operatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However a quarter of patients in Guthrie et al ’s study were non-domicile and may represent different ethnicity. Mastropasqua et al have shown that black patients have poorer visual outcomes compared with white and Asian patients, and this may explain our outcomes in an exclusively black population 24. A preoperative intravitreal injection of bevacizumab has been demonstrated by Guthrie et al in an African population to reduce intraoperative complications and reduce vision loss after vitrectomy 23.…”
Section: Discussionmentioning
confidence: 89%
“…However, the exact number and nature of the genes involved or the epigenomics elements that are involved remain elusive. Other demographic risk factors for DR include Hispanic or African American ethnicity, systemic hypertension, duration of disease, and pregnancy ( Gupta and Misra, 2016 ; Penman et al, 2016 ; Varma et al, 2016 ; Davidson, 2017 ; Jin et al, 2017 ; Kowluru, 2017 ; Mastropasqua et al, 2017 ; Zhang et al, 2017 ). DME is one of the most common complications and the cause of vision loss in diabetics.…”
Section: Introductionmentioning
confidence: 99%